Types And Functions of Code Switching Found in Deddy Corbuzier’s Podcast on Spotify - Ni Wayan Suastini; I Gusti Agung Sri Rwa Jayantini; Felia Gita Dewi, Ni Kadek (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Nowadays, combining two languages in the communication process often occurs in the bilingual community that is called code-switching. This study concerned code-switching in Deddy Corbuzier’s utterances on his PodCast. This study has specific aims (1) to find out the types of code-switching used by Deddy Corbuzier on his Podcast; (2) to identify the functions of code-switching used in Deddy Corbuzier’s utterances. This study is concerned with code-switching Indonesian-English language in Deddy Corbuzier utterances in PodCast on Spotify. A qualitative method is used for this study for analyzing the data collected from ten podcasts. The method is applied to give a clear description of the data according to the theory proposed by Poplack (1980) as cited in Romaine (1989: 122) and the theory proposed by Appel and Muysken (1987). Type of code-switching which is intra-sentential switching is the most often used in Deddy Corbuzier utterances because Deddy Cobuzier is more comfortable when using words, clauses, and phrases in one sentence to convey motivational messages. Metalinguistic is the dominant function of code-switching in Deddy Corbuzier’s utterances with 76 data (46,79%) as the final result of this study. It occurs because Deddy Corbuzier wanted to impress the other participants with a show of linguistic skill.